El Salvador : 2010 Article IV Consultation and First Review Under the Stand-By Arrangement; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report ;, 2010)
The Salvadoran economy was severely affected by the global economic slowdown. Further strengthening the economy's growth prospects and reducing poverty will depend on a durable fiscal consolidation effort and improvements in the investment climate through continued commitment to macroeconomic and financial stability. A recent IMF/World Bank Financial System Stability Assessment (FSSA) confirmed that the Salvadoran financial system withstood the global financial crisis well and was well capitalized and liquid. The FSSA recommended enhancements to the legal and regulatory frameworks as well as measures to reduce some remaining vulnerabilities.